2008
DOI: 10.1196/annals.1428.075
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Nematocidal Activity of Plant Extracts of Mexican Flora against Haemonchus contortus Fourth Larval Stage

Abstract: Fourteen plant extracts were evaluated in vitro against the fourth larval stage of Haemonchus contortus. The plants species used were Tagetes erecta, Argemone mexicana, and Castela tortuosa. The assays were run in 24-well cell culture plates at room temperature with three replicates. After exposure, aliquots were taken from the corresponding wells and transferred to a microscope for observation. Evaluation criteria were based on the average of live and/or dead larvae. ANOVA test and Tukey test were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Similarly, plants and their derivatives are being profoundly researched for efficacy against animal parasites. Several plants are currently being investigated to identify available anthelmintic agents for using in animals (Aguilar et al, 2008;Shai et al, 2009;Alonso-Díaz et al, 2010). Soro et al (2013) also reported anthelmintic efficacy of Anogeissus leiocarpus Guill & Perr (Combretaceae) and improvement of body weight after in vivo treatment in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, plants and their derivatives are being profoundly researched for efficacy against animal parasites. Several plants are currently being investigated to identify available anthelmintic agents for using in animals (Aguilar et al, 2008;Shai et al, 2009;Alonso-Díaz et al, 2010). Soro et al (2013) also reported anthelmintic efficacy of Anogeissus leiocarpus Guill & Perr (Combretaceae) and improvement of body weight after in vivo treatment in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that after 96 hours exposure, T. erecta acetonic plant extract produced 99.7 % lethal activity on the fourth larval stage of Haemonchus contortus , followed by Castela tortuosa hexane extract (85.8 %) and T. erecta methanol extract (58.3 %) (Aguilar et al 2008 ). Commercially available Aztec Marigold ( Tagetes erecta ) fl ower extract exhibited in vitro antioxidant activity and in vivo dose-dependent analgesic effect on acetic-acid-induced abdominal writhing (Bashir and Gilani 2008 ).…”
Section: Anthelminthic Activitymentioning
confidence: 99%
“…Nematocidal: acetonic flower extract produced 99% lethal activity in vitro against fourth larval stage of Haemonchus contortus after 24 h (Aguilar et al, 2008). Antimicrobial: aqueous and organic root extracts demonstrated significant activity in vitro against three Gram-positive and two Gram-negative bacteria and 2 fungal strains with MIC ranging 12.5-100 mg/ml (Gupta and Vasudeva, 2010).…”
Section: Consensus Analysismentioning
confidence: 99%